Neuronal E93 is required for adaptation to adult metabolism and behavior - Cecilia Yip; Steven C. Wyler; Katrina Liang; Shin Yamazaki; Tyler Cobb; Maryam Safdar; Aarav Metai; Warda Merchant; Robert Wessells; Adrian Rothenfluh; Syann Lee; Joel Elmquist; et al. (Elsevier, 2024)
Objective: Metamorphosis is a transition from growth to reproduction, through which an animal adopts adult behavior and metabolism. Yet the neural mechanisms underlying the switch are unclear. Here we report that neuronal E93, a transcription factor essential for metamorphosis, regulates the adult metabolism, physiology, and behavior in Drosophila melanogaster. Methods: To find new neuronal regulators of metabolism, we performed a targeted RNAi-based screen of 70 Drosophila orthologs of the mammalian genes enriched in ventromedial hypothalamus (VMH). Once E93 was identified from the screen, we characterized changes in physiology and behavior when neuronal expression of E93 is knocked down. To identify the neurons where E93 acts, we performed an additional screen targeting subsets of neurons or endocrine cells. Results: E93 is required to control appetite, metabolism, exercise endurance, and circadian rhythms. The diverse phenotypes caused by pan-neuronal knockdown of E93, including obesity, exercise intolerance and circadian disruption, can all be phenocopied by knockdown of E93 specifically in either GABA or MIP neurons, suggesting these neurons are key sites of E93 action. Knockdown of the Ecdysone Receptor specifically in MIP neurons partially phenocopies the MIP neuron-specific knockdown of E93, suggesting the steroid signal coordinates adult metabolism via E93 and a neuropeptidergic signal. Finally, E93 expression in GABA and MIP neurons also serves as a key switch for the adaptation to adult behavior, as animals with reduced expression of E93 in the two subsets of neurons exhibit reduced reproductive activity. Conclusions: Our study reveals that E93 is a new monogenic factor essential for metabolic, physiological, and behavioral adaptation from larval behavior to adult behavior.